A semi-floating gate AlGaN/GaN HEMT for normally-off operation. (July 2022) - Zhang, Lin-Qing; Wu, Zhi-Yan; Wang, Peng-Fei
Abstract: AlGaN/GaN-Si based HEMTs are considered as the promising candidates for application in the 5G communication system due to their excellent characteristics and low cost. Enhancement mode (E-mode) AlGaN/GaN HEMTs should be fabricated for power application. In this paper, we report a novel semi-floating gate (SFG) AlGaN/GaN HEMT with 20 nm Al2 O3 which acts as control gate capacitance for normally-off operation. This methods avoids gate recess process which may damage the 2DEG channel. Also, the Vth can be programmed to different values by adjusting the VCGP . In our results, by adjusting control gate voltage VCGP  = 15 V, the Vth of AlGaN/GaN HEMT on PCB (containing capacitances with different capacitance values which acts as control gate capacitance) is extracted to exceed over 8.5 V at VDS  = 15 V. In addition, for the fabricated SFG AlGaN/GaN HEMT with the Al2 O3 thickness of 20 nm, the Vth of the fabricated SFG AlGaN/GaN HEMT is extracted to be 0.42 V when VCGP increases up to 5 V. The SFG AlGaN/GaN HEMT technique presented in our results offer a prospective method to fabricate E-mode AlGaN/GaN HEMTs.